Dual-band polarization-sensitive terahertz metamaterial absorber possessing frequency and amplitude dynamically-continuously tunable characteristics. Issue 1 (11th June 2022) - You, Li; Xuan, Wang
Abstract: In order to suit the increasingly complex electromagnetism environment, multifunctional and continuously tunable terahertz device is becoming a research focus. In this paper, a frequency and amplitude tunable dual-band terahertz metamaterial absorber is proposed. Continuous tuning of absorption frequency and amplitude are completed by dynamic control of the conductivity of photosensitive silicon and the polarization angle, respectively. The tuning range of 55 GHz and amplitude modulation depth up to 100% are obtained. It can be concluded that the structure provides a new approach for the realization of future terahertz metamaterial absorbers possessing the characteristics of multifunction, portability, and intelligence.